Social Media in Business Communication and Literature - PALIATH, GAYATHRI (International Journal of Psychosocial Rehabilitation, 2020)
This article covers impact of social media on two aspects, viz., Business Communication and Literature. Businesses are realising the importance of social media for internal and external communication. Social media offers flexibility in time for customer interactions, and easy and cost-efficient way of reaching out to customers. Social media help two-way communication between the businessmen and their customers. Businesses should track the consumer feedback on social media and respond quickly to negative feedback. Criticism that social media kills the reading habits and English language capabilities of the modern generation stems from a misunderstanding of the nature and usage of literature. Languages benefit from adapting and adopting to changes. Writers always strive to extend the boundaries. Social media literature is a new genre not just in terms of the media, but in terms of the structure and style of writing.